PERANCANGAN SISTEM INFORMASI SIMPAN PINJAM PADA K.S.U JAYA RAYA PONTIANAK BERBASIS WEB - Septian Septian; Daning Nur Sulistyowati (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2021)
K.S.U Jaya Raya is the cooperative of savings and loan whose membership includes local people who apply for loans for business capital. K.S.U Jaya Raya is still recapitulating the savings and loan transactions that are sourced from notes and then copied to Ms. Excel for reporting. The implemented data processing requires a lot of energy and time, errors in data processing that have an impact on the quality of information in the report. Therefore, this study contains the design of a savings and loan information system that uses the waterfall model as a software development model consisting of analysis, design, coding, testing and support. Data collection techniques used consisted of observation, interviews and literature study. This system provides facilities for two (2) levels of access, consist of admin and finance department. Admin able to manage member account data, loans, installments, loan and installment reports, list of term deposits, deposit deposits, withdraw deposits, deposit reports, operational costs and operational expense reports. The finance department able to manage loan types, types of deposits, users, opening balances, access loan reports, installment reports, savings reports, operating expense reports, general journals, ledgers, trial balances, reports of remaining operating results, and balance sheets.